Policy formulation crime contempt of court based on the national criminal code - Zulfa, Maulidza Diana; Raharjo, Eko; Shafira, Maya (Dynamics of Politics and Democracy, 2022)
Purpose: The aim of this research is to analyze the regulation of the Contempt of Court criminal acts based on the National Criminal Code, and to analyze the policy formulation of the Contempt of Court criminal acts based on the National Criminal Code. Research methodology: This study is a type of Normative Juridical and Empirical Juridical research. Normative jurisdictional research is carried out based on legal materials such as legal theory, legal principles, and legislation related to research. Results: Based on the results of research and data obtained when conducting interviews with several sources, the author believes that the Contempt of Court problem is closely related to criminal law policy (penal policy), especially at the formulation stage, namely, the stage of determining what actions will be made into criminal acts and determining sanctions. Limitations: The Contempt of Court regulations in the previous Criminal Code, which is a colonial legacy, is still unclear and does not specifically regulate the Contempt of Court acts. Existing regulations in positive law regarding the Act of Contempt of Court are still being debated regarding the definition and classification of an act that is considered to undermine the authority and insult the judicial process. Contributions: This study highlights the need for legal reforms that adapt to societal conditions. In an effort to enforce the law, as is the offense of the Contempt of Court in the National Criminal Code, which has undergone changes to suit the current situation of Indonesian society.